2018
DOI: 10.3390/en11040983
|View full text |Cite
|
Sign up to set email alerts
|

Economic Performance and Emission Reduction of Supply Chains in Different Power Structures: Perspective of Sustainable Investment

Abstract: Environmental issues have increasingly received attention in both industry and academia. Many firms have started to make sustainable investments, such as adopting the pollution-abatement technologies, to reduce carbon emissions. To investigate the impacts of the sustainable investment on firms' profit and emission reduction, we consider supply chains with uncertain demand in different power structures. Specifically, we examine the sustainable investment problem in three supply chain power structures, i.e., man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…To fulfill social and environmental responsibility and meet consumers' expectations, firms in various industries have begun to invest in sustainability projects, such as reducing carbon/pollution emissions during the manufacturing process and improving the greenness of products by adopting recyclable materials [11,12]. For example, Apple has allocated a $1.5 billion green bond dedicated to financing sustainability projects since 2011, which has resulted in an 8.9-million-ton reduction of their carbon footprint in 2016 alone [13,14]. H&M, the Sweden fast fashion company, has introduced organic cotton into product development and clean technology to reduce pollution and carbon emissions in its manufacturing process [15].…”
Section: Introductionmentioning
confidence: 99%
“…To fulfill social and environmental responsibility and meet consumers' expectations, firms in various industries have begun to invest in sustainability projects, such as reducing carbon/pollution emissions during the manufacturing process and improving the greenness of products by adopting recyclable materials [11,12]. For example, Apple has allocated a $1.5 billion green bond dedicated to financing sustainability projects since 2011, which has resulted in an 8.9-million-ton reduction of their carbon footprint in 2016 alone [13,14]. H&M, the Sweden fast fashion company, has introduced organic cotton into product development and clean technology to reduce pollution and carbon emissions in its manufacturing process [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dong et al [25] studied the sustainability investment considering the cap-and-trade regulation, and pointed out that operational decisions are greatly affected by sustainability investment efficiency. Shi et al [26,27] examined how the power structure affects sustainability investment efficiency, and found that the partner with less power in a supply chain has more incentives to invest sustainably. Although those studies focus on sustainability issues, our paper is different in that we mainly discuss how the environment is affected under a setting of remanufacturing, and in such settings we also consider the environmental awareness in the customer choice model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effects of energy consumption and healthcare supply chain management were not included in the study. Shi et al [48] incorporated the development of a supply chain with demand uncertainty in different power structures to investigate the effect of sustainable investment on profit and emissions. Energy and healthcare issues were not addressed.…”
Section: Traditional Supply Chain Management With a Single Objectivementioning
confidence: 99%